Formation of heterostructures via direct growth CN on h-BN porous nanosheets for metal-free photocatalysis. (December 2017) - He, Zuoli; Kim, Chuhyung; Lin, Lihua; Jeon, Tae Hwa; Lin, Sen; Wang, Xinchen; Choi, Wonyong
Abstract: Many recent advances in creating heterostructures based on 2D materials have opened new possibilities in catalysis. This study prepared a new 2D hybrid photocatalyst (CBN-x) consisting of CN and h- BN using low-cost precursors (urea and boric acid). The effects of CN loading on the structure, surface chemistry and photocatalytic activities were systematically investigated. The photocatalytic activities of CBN-x samples were tested for the production of H2 and H2 O2, which demonstrated markedly enhanced activities without the need of noble metal co-catalysts. However, CBN-x activities for the photocatalytic oxidation of organic compound were not better than that of h-BN. Loading CN on h- BN sheets, C 2p and N 2p orbitals from CN introduce new valence and conduction band edges, which gradually narrowed the bandgap and enhanced light absorption efficiency of the hybrid photocatalysts. In such metal-free systems, electrons generated in CN transfer to h-BN, while photogenerated holes on h- BN transfer to CN, which enhances the charge separation through the heterojunction interface (CN/BN). Therefore, increasing the CN loading enhances the overall efficiency of photocatalysis until excessive loading of CN covers the active sites on h-BN. Graphical abstract: Highlights: In this work, we introduced a new kind of 2D heterojunction created by loading CN on h-BN nanosheets. The effects of CN loading on the surface chemistry and photocatalytic activities were systematically investigated. Photocatalytic H2 and H2 O2 production activities of hybrid CBN-x samples were proven to be enhanced. We carried out first-principle calculations which revealed the unique physical features of CN/BN heterostructures.